Nilai Pendidikan Agama Hindu Dalam Lontar Siwa Sasana - Ida Bagus Putu Eka Suadnyana; I Putu Ariyasa Darmawan (Jayapangus Press, 2020)
Hinduism in addition to giving teachings also guides its people to achieve happiness and harmonize their lives physically and spiritually. Efforts to maintain the preservation of Religion can be done through strengthening education in the field of religion. For people in Bali this is the basic capital as a mental and spiritual driving force and is a guide, guide and impetus in humans to achieve a better and perfect quality of life. The teachings of Hinduism are based on the Vedic scriptures, but also in secondary books, one of which is the ancient manuscripts in the form of Lontar. Dealing with this, the author intends to examine in depth in terms of the value of Hindu religious education for a lontar, namely lontar